Diagnostic Performance of Real-Time Elastography in the Assessment of Advanced Fibrosis in Chronic Hepatitis C - Susana Marques; Joana Carmo; Maria Ana Túlio; Miguel Bispo; Leopoldo Matos; Cristina Chagas (GE: Portuguese Journal of Gastroenterology, 2016)
Background and aims: Since liver fibrosis index (LFI) was developed by Fujimoto et al., real-time elastography (RTE) has become a promising non-invasive technique to assess fibrosis in chronic hepatitis C (CHC). The aims of this study were to compare the diagnostic performance of RTE versus laboratory tests to predict advanced fibrosis (METAVIR scoring system: F ≥ 3) in patients with CHC, using liver biopsy (LB) as the reference standard; and to evaluated the impact of patient anthropometric features on RTE histogram acquisition. Methods: This prospective study included 37 patients with CHC scheduled for LB. Aspartate aminotransferase (AST)/alanine aminotransferase (AST) ratio, AST/platelet ratio index (APRI), and Fibrosis-4 index (FIB-4) were calculated from recent (≤6 months) laboratory data. RTE was performed by two independent operators blind to each other’ findings and to LB results, using Hitachi HI-VISION Avius ultrasound system. According to Hitachi RTE software, liver elasticity was evaluated through the LFI. Percutaneous ultrasound-assisted LB was performed in the same day of RTE. All LB specimens were analyzed by an expert pathologist blind to RTE results. Hepatic fibrosis was staged according to METAVIR scoring system. The diagnostic performance of the LFI, AST/ALT ratio, APRI and FIB-4 for predicting advanced fibrosis was assessed using area under receiver-operating characteristic curve (AUROC), sensitivity, specificity, positive-predictive and negative-predictive (NPV) values. Results: Thirty-seven LB were performed without complications. The distribution according to METAVIR scoring system was F0–1 in 13 patients (35%), F2 in 13 (35%), F3 in 9 (25%) and F4 in 2 (5%). Thirty-seven RTE procedures were performed. Histogram acquisition was successfully achieved in 32 patients (86%). Abdominal wall thickness ≥23 mm was associated with no histogram acquisition (p = 0.018). Using the optimal cut-off value of 2.38, the AUROC for the LFI was 0.73. The AUROC for the AST/ALT ratio, APRI and FIB-4 were 0.62, 0.79, and 0.82, respectively. Conclusions: The LFI calculated by RTE showed a very good diagnostic performance to predict advanced fibrosis in CHC, with remarkable sensitivity and NPV (both 100%).